Assessment of the adequacy of breastfeeding in infants and the features of the introduction of complementary feeding - A. F. Kiosov (Лечащий Врач)
Background. The dynamics of body weight is one of the main criteria for the adequacy of breastfeeding in newborns and infants. In the neonatal period, the loss of body weight (BMI) of a child after birth is assessed. Indicators of BMI greater than 10% of birth weight, as well as the retention of BMI over the age of 10 days of life may indicate a child's malnutrition. The average daily weight gain in children under 3 months of age should be 26-30 g., at the age of 3 to 6 months – 17-18 g. With adequate feeding, infants' urine should be light, transparent, odorless, and urinate at least 5-6 times a day. With insufficient nutrition, children may develop hypoglycemia, jaundice associated with insufficient intake of breast milk, hypernatremia, polycythemia, and dehydration. With the progression of dehydration, there is an increase in plasma osmolarity, total serum protein, an increase in the relative density of urine, and oliguria. It should be remembered that many clinical signs are not specific and may be associated not only with malnutrition, but also with defects in child care and the development of diseases.Conclusion. Medical professionals must have the professional knowledge and competencies to perform differential diagnosis. A child with signs of malnutrition should be prescribed additional nutrition or supplementation in a timely manner. Mother's expressed milk, donor milk, and children's adapted milk formulas can be used for additional feeding. The introduction of supplementary feeding is necessarily carried out against the background of support and stimulation of lactation in the mother. If there are signs of dehydration, you can give the baby extra water between feedings. In children aged 4 to 6 months with malnutrition, complementary foods may be prescribed, preference is given to industrial baby porridges.